Editorial on Asymptomatic Rib Fractures and Their Relationship to Child Abuse - Oliver J. Muensterer; Eva Möhler (MDPI AG, 2024)
Children recently published a Special Issue that focuses on child abuse and neglect as severe adverse childhood experiences [...]